1987
DOI: 10.1111/j.1600-051x.1987.tb01534.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy of listerine in inhibiting and reducing plaque and experimental gingivitis

Abstract: 103 adult subjects completed a supervised 2-week double-blind controlled clinical study to determine the effect of using either listerine antiseptic (LA) or its vehicle control (VC), as the only oral hygiene procedure, in inhibiting the development of and in reducing plaque and experimental gingivitis. Following baseline examinations, half-mouth prophylaxes were performed on each subject, who continued normal oral hygiene and returned 4 or 5 days later for a second baseline. Subjects then rinsed, under supervi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
21
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 10 publications
4
21
0
Order By: Relevance
“…The present study confirms the antiplaque and antigingivitis efficacy of an EO mouthrinse which has been demonstrated in short-term, 7,8,9 as well as in longer-term studies 6,10,11,12,13 following the ADA guidelines for clinical trials. These studies showed up to 56% greater plaque reduction and up to 34% greater gingivitis reduction than control in subjects with mild-to-moderate plaque and gingivitis.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The present study confirms the antiplaque and antigingivitis efficacy of an EO mouthrinse which has been demonstrated in short-term, 7,8,9 as well as in longer-term studies 6,10,11,12,13 following the ADA guidelines for clinical trials. These studies showed up to 56% greater plaque reduction and up to 34% greater gingivitis reduction than control in subjects with mild-to-moderate plaque and gingivitis.…”
Section: Discussionsupporting
confidence: 88%
“…Clinical trials utilizing experimental gingivitis models have been frequently used as a short-term model to evaluate the antiplaque and antigingivitis efficacy of mouthrinses containing antimicrobial agents. These trials have tested a fixed combination of essential oils, 8,9 0.12% chlorhexidine gluconate, 25,26 cetylpyridinium chloride, 27 0.1% hexetidine, 28 and other noncommercial antimicrobial agents. 29 Therefore, there is enough evidence to support that experimental gingivitis study designs, like long-term models, have been accepted as a valid model to determine and compare efficacy of antiseptic mouthrinses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…sential oils [12][13][14] and to demonstrate superiority to 0.05% CPC rinses. 15 This experimental gingivitis model is useful as a short-term model to determine efficacy of mouthrinse formulations and has been found to be consistent with six-month clinical trials results.…”
Section: Introductionmentioning
confidence: 99%
“…This data confirmed that rinsing regularly with an EOcontaining mouthrinse twice a day can reduce the level of blood-borne bacteria caused by a standardized challenge such as that of chewing an apple. It seems reasonable to assume that maintaining good oral hygiene practices, including tooth brushing, flossing and using an effective antimicrobial mouthrinse agent regularly, contributes to preventing periodontal disease, [7][8][9][10][11][12] which, in turn, leads to a lower risk of developing bacteremia.…”
Section: Discussionmentioning
confidence: 99%